Thermal power stations and their application for preparation of geopolymers and zeolitic compounds - Temuujin, J.; Rickard, William; Riessen, A. (2012)
Mongolia has some of the world's largest coal reserves with an estimated total coal reserve of over 150 billion tonnes. At present, over 90% of Mongolian electricity is produced by combined heat and thermal power stations. The main coal deposits used for Central power system's power stations are Baganuur, Shivee-ovoo lignite type coal and Shariin gol bituminous coal. In Mongolia almost 600,000 tonnes of coal combustion by-products are disposed of in waste ponds. In this research, we have thoroughly characterized Mongolian coal combustion by-products including fly ashes sourced directly from thermal power stations and ash retrieved from ponds. It was determined that fly ashes generated from Baganuur and Shivee-ovoo coal deposits are class C, while ash from Shariin gol coal is class F (according the ASTM C618). All ash products were characterized by chemical, mineralogical, granulometrical, porosity, FE-SEM and radiation methods. Fly ashes sourced directly from power stations were found to be more suitable for manufacture of geopolymers for building materials application and zeolite synthesis than ashes retrieved from ash ponds. The adsorption and porous properties of zeolitic compounds were measured and found to be suitable for adsorption of Cr6+ from simulated tannery waste water.